Intangible Asset Management in the Perspective of Higher Education Management - Asnawi, Asnawi; Nurhidayati, Viati; Cahyono, Agus Dwi; Fadoli, A. (CV. Civiliza Publishing, 2026)
Intangible assets have become strategic resources in higher education institutions, particularly in strengthening institutional performance, competitiveness, and sustainability. This study aims to examine the concept and role of intangible asset management in the perspective of higher education management through a comprehensive literature-based analysis. Using a qualitative approach with a library research design, this study analyzes scholarly articles, academic books, and reputable publications related to intangible assets, intellectual capital, and higher education management. Data were collected from open-access and indexed academic databases and analyzed using content analysis techniques to identify key themes and conceptual patterns. The findings indicate that intangible assets in higher education consist of human capital, structural capital, and relational capital, which interact synergistically in creating institutional value. Human capital plays a crucial role in enhancing academic quality and innovation, structural capital ensures the institutionalization of knowledge through governance systems and policies, while relational capital strengthens reputation and stakeholder trust. The study concludes that effective management of intangible assets requires an integrative and strategic approach rather than a fragmented administrative practice. This research contributes conceptually by offering a holistic framework for managing intangible assets in higher education and provides practical insights for university leaders in developing sustainable institutional strategies.